2021
DOI: 10.1007/s00268-021-06055-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Surgeons Working Smarter or Harder? A Systematic Review Comparing the Physical and Mental Demands of Robotic and Laparoscopic or Open Surgery

Abstract: Background Minimally invasive surgical techniques such as robotic surgical platforms have provided favourable outcomes for patients, but the impact on surgeons is not well described. This systematic review aims to synthesize and evaluate the physical and mental impact of robotic surgery on surgeons compared to standard laparoscopic or open surgery. Methods A search strategy was developed to identify peer-reviewed English articles published from inception to end of December 2019 on the following databases: MEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…In fact, MIS offers a shared view of the surgical field and gives the opportunity to the entire team to understand the procedure and monitor the operation progress, but it needs the establishment of a new interpersonal routine [ 107 ]. Laparoscopy is burdened by the physical stress of the surgical team, whereas robotic surgery offers a less physically demanding approach, but introduces a console creating a physical distance of the surgeon from the team, mediating communication through a microphone [ 108 , 109 ]. In this context and maybe more in an emergency scenario, a team of well-trained people is the key factor for a successful robotic program [ 110 ] and should represent the standard also in emergency MIS.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, MIS offers a shared view of the surgical field and gives the opportunity to the entire team to understand the procedure and monitor the operation progress, but it needs the establishment of a new interpersonal routine [ 107 ]. Laparoscopy is burdened by the physical stress of the surgical team, whereas robotic surgery offers a less physically demanding approach, but introduces a console creating a physical distance of the surgeon from the team, mediating communication through a microphone [ 108 , 109 ]. In this context and maybe more in an emergency scenario, a team of well-trained people is the key factor for a successful robotic program [ 110 ] and should represent the standard also in emergency MIS.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results of some studies showed that the workload in laparoscopic surgery was higher than that in open surgery, the difference was not statistically significant (Yu et al 2016 ; Law et al 2020 ). A recent systematic review (2021) showed varied physical and mental outcomes among robotic, laparoscopic, and open surgical techniques due to methodological differences (Park et al 2021 ). However, the high workload in the open surgery technique in the present study can be related to the complexity and long duration of the open surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption of verbal and non-verbal cues causes teams to figure out novel solutions to navigate around these new challenges and are documented in the literature as having the ability to cause frustration for surgeons if verbal acknowledgement is not made (Catchpole et al, 2019). Although physical workload has been cited as lower in robotic surgery compared to traditional laparoscopic or open-surgery methods in surgeons (Law et al, 2020), most studies show mixed outcomes in relation to physical and mental demands, likely due to varying methodologies to assess intraoperative workload (Park et al, 2021). In order to continue evaluating the challenges associated with organizations adopting robotic-assisted surgery, such as identifying variations of cognitive demands between different surgical roles (e.g., circulating nurses, scrub technicians.…”
Section: Workload In Surgerymentioning
confidence: 99%